Dosimetric considerations for moldable silicone composites used in radiotherapy applications. Issue 6 (18th April 2022) - Aldosary, Ghada; Belec, Jason; Foottit, Claire; Vandervoort, Eric
Abstract: Due to their many favorable characteristics, moldable silicone (MS) composites have gained popularity in medicine and recently, in radiotherapy applications. We investigate the dosimetric properties of silicones in radiotherapy beams and determine their suitability as water substitutes for constructing boluses and phantoms. Two types of silicones were assessed ( ρ ρ = 1.04 g/cm 3 and ρ ρ = 1.07 g/cm 3 ). Various dosimetric properties were characterized, including the relative electron density, the relative mean mass energy‐absorption coefficient, and the relative mean mass restricted stopping power. Silicone slabs with thickness of 1.5 cm and 5.0 cm were molded to mimic a bolus setup and a phantom setup, respectively. Measurements were conducted for Co‐60 and 6 MV photon beams, and 6 MeV electron beams. The doses at 1.5 cm and 5.0 cm depths in MS were measured with solid water (SW) backscatter material ( D MS–SW ), and with a full MS setup ( D MS–MS ), then compared with doses at the same depths in a full SW setup ( D SW–SW ). Relative doses were reported as D MS–SW / D MS–SW and D MS–MS / D SW–SW . Experimental results were verified using Monaco treatment planning system dose calculations and Monte Carlo EGSnrc simulations. Film measurements showed varying dose ratios according to MS and beam types. For photon beams, the bolus setup D MS–SW / D SW–SW exhibited a 5% relative dose reduction. The dose for 6 MV beams was reduced by nearly 2% in a full MS setup. Up to 2% dose increase in both scenarios was observed for electron beams. Compared with dose in SW, an interface of MS–SW can cause relatively high differences. We conclude that it is important to characterize a particular silicone's properties in a given beam quality prior to clinical use. Because silicone compositions vary between manufacturers and differ from water/SW, accurate dosimetry using these materials requires consideration of the reported differences.